Electromyographic Features in a Chinese Cohort With Hereditary Skeletal Muscle Channelopathies. Issue 3 (May 2020) - Sun, Jian; Luo, Sushan; Song, Jie; Huang, Jun; Cai, Shuang; Zhu, Wenhua; Zhou, Lei; Xi, Jianying; Lin, Jie; Lu, Jiahong; Xu, Minjie; Dou, Tonghai; et al.
Abstract : Purpose: Hereditary skeletal muscle channelopathies are characterized by muscle stiffness and/or periodic muscle weakness because of different gene mutations. The objective of this study was to investigate the clinical and electromyographic phenotypes in Chinese patients with different skeletal ion channel mutations. Methods: The electromyographic results of 61 Chinese patients with skeletal muscle channelopathies were retrospectively reviewed and the differential features were characterized. Results: Myotonic discharges were in patients with chloride voltage-gated channel 1 and sodium voltage-gated channel alpha subunit 4 mutations. Subclinical myotonia was identified in four patients with hypokalemic periodic paralysis because of sodium voltage-gated channel alpha subunit 4 mutations. Patients with potassium voltage-gated channel subfamily J member 2 mutations had an early decline after exercise (5.7 ± 4.9 minutes) and patients with calcium voltage-gated channel subunit alpha 1S mutations have a relatively lower baseline amplitude (4.6 ± 2 mV). Specific patterns were characterized in patients with Becker disease and paramyotonia congenital after short exercise. Conclusions: Myotonic discharges help to discriminate chloride and sodium from other channelopathies. Early decline and low baseline compound motor action potential amplitude in long exercise test are significant in patients with potassium voltage-gated channel subfamily J member 2 and calcium voltage-gated channel subunit alpha 1S mutations, respectively. Electromyographic patterns in the electromyography study and exercise test may help in better providing the comprehensive picture for patients with primary skeletal muscle channelopathies. Abstract : Supplemental Digital Content is Available in the Text.